2013
DOI: 10.1016/j.apcata.2013.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Production of biodiesel from mixed waste vegetable oils using Ferric hydrogen sulphate as an effective reusable heterogeneous solid acid catalyst

Abstract: Biodiesel production by simultaneous esterification and transesterification of waste oil with methanol has been studied in a heterogeneous system using solid ferric hydrogen sulphate [Fe (HSO4)3] acid catalyst. The catalyst was prepared by displacement reaction followed by calcination at 400 °C for 3 h. The prepared catalyst was characterized using X-ray diffraction (XRD), Fourier transform infrared spectrometer (FT-IR), Brunner-Emmett-Teller surface area measurement (BET), thermal gravimetric analyzer (TGA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 30 publications
2
50
0
1
Order By: Relevance
“…A total of 7.5 kg of oil was used for the optimization of biodiesel production process. The materials ferric nitrate nonahydrate, manganese nitrate tetra hydrate and ammonium molybdate tetra hydrate 99.0 , zirconium oxy chloride and ammonium hydroxide 28 -30 were obtained from Sigma-Aldrich-Malaysia and employed in the preparation of the catalyst 13,14 .…”
Section: Chemicals and Materialsmentioning
confidence: 99%
“…A total of 7.5 kg of oil was used for the optimization of biodiesel production process. The materials ferric nitrate nonahydrate, manganese nitrate tetra hydrate and ammonium molybdate tetra hydrate 99.0 , zirconium oxy chloride and ammonium hydroxide 28 -30 were obtained from Sigma-Aldrich-Malaysia and employed in the preparation of the catalyst 13,14 .…”
Section: Chemicals and Materialsmentioning
confidence: 99%
“…Biodiesel property values can be checked by verifying it with the ASTM D6751 standard shown in table 4 [22,23,24,25,26]. Biodiesel produced seems to be matched with that of the ASTM D6751 biodiesel standard.…”
Section: Comparison Of Propertiesmentioning
confidence: 99%
“…Studieshave shown that biodiesel being less polluting, non-toxic and biodegradable; it can be used directly in most diesel engines without much engine modifications. Biodiesel is commonly produced by transesterification of lipids, animal fats, grease and waste cooking oils [1,2,3,4,5,6,7,8,9,10,11,12,13].Catalyst plays an important role in transesterification reactions. Homogeneous catalysts result in the formation of soap which makes more complication in the reaction and also in the product separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the waste cooking oil was heated at temperature in range of 100-108 to get rid of water by loss and food debris through filtration. The free fatty acid FFA content was determined by a standard titration method 10 .…”
Section: Pre-treatment Of Waste Cooking Oilmentioning
confidence: 99%